PENINGKATAN HASIL BELAJAR AL-QUR’AN HADITS SISWA KELAS XI DENGAN METODE PQ4R: PREVIEW, QUESTION, READ, REFLECT, RECITE, REVIEW DAN TUTOR SEBAYA DI MA DARUL AMANAH BEDONO - Anggreyani, Adhe Lia (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2025)
This classroom action research aimed to improve students’ learning outcomes in the subject of Al-Qur’an Hadith among eleventh-grade students at MA Darul Amanah Bedono through the implementation of the PQ4R (Preview, Question, Read, Reflect, Recite, Review) learning method in collaboration with peer tutoring. The initial condition showed that only 2 out of 7 students (28.57%) achieved the Minimum Mastery Criterion (KKM), while most students remained passive in conventional lecture-based and memorization-oriented learning activities. After applying the PQ4R method in Cycle I, the number of students who achieved mastery increased to 4 students (57.14%), with the class average score improving to 73.28. In Cycle II, the use of Chromebook-based digital learning media further enhanced the effectiveness of the learning process, resulting in 6 out of 7 students (85.71%) achieving the mastery level. The teacher and student observation scores also increased to 3.8 and 3.6, respectively. The findings indicate that the integration of the PQ4R method with peer tutoring effectively improved students’ comprehension, participation, and learning motivation. Moreover, this collaborative approach provided practical benefits for teachers by fostering a more interactive, engaging, and meaningful learning environment in the Al-Qur’an Hadith classroom.